CLONING AND EXPRESSION OF A PARTIAL UREA ANTIGEN FOR THE PRODUCTION OF VACCINE AGAINST HELICOBACTER PYLORI, THE RISK FACTOR FOR GASTRIC CANCER - Mehran, Mohammad Javad; Zendehbad, Seyed Hossein; Malla, Sudhakar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Helicobacter pylori, a gram-negative, microaerophilic, motile, spiral-shaped bacterium, have been established as the etiologic agent of chronic gastritis and belongs to phylum Proteobacteria. Infection with H. pylori is the primary identified cause of gastric cancer. H.pylori has the capacity to invade the stomach and tolerate the habitat of the stomach. But eventually the organism dies slowly due to the low pH in the stomach. In order to protect itself from the acidic environment it produces loads of urease enzyme. This urease enzyme has drawn attention all round the world as a diagnostic agent in detecting the helicobacter infection. And moreover the antibiotic based drugs are of limited use. Novel methods are being developed for the production of antibodies to specific antigens and thus helping in the process of development of protein based vaccines. UreA (Urease) gene was isolated and ligated into pTZ57R/T cloning vector. The ligated product was then cloned into DH5α strain and allowed to propagate. The plasmids thus cloned were purified and later expressed for the gene of interest in an expression vector. The proteins specific to the gene of interest was then isolated and purified. This proteins purified can in turn be used for protein based vaccines. Key words: ureA gene, Helicobacter pylori, cloning, expression proteins.